Systematic analysis and usage of harmful resources. (July 2020) - Sheu, D. Daniel; Yen, Ming-Zai
Highlights: Novel systematic process to convert harmful resources for useful applications. Incorporate zero waste concept into a general TRIZ resource philosophy. Provide structured forms to facilitate practical applications. Abstract: The concept of resources in TRIZ (Theory of Inventive Problem Solving) is to make the most use of existing resources to solve problems with zero or minimum cost. Even though resources are one of the most powerful concepts in the TRIZ tools, there have been few systematic methods to identify resources for problem solving. This research established a systematic process to analyze harmful resources and identify opportunities for converting the harmful resources to useful applications or using the useful part of the harmful resource while avoiding or being insensitive to its harmful aspects. The systematic process integrates inverse function oriented search, function attribute analysis, and effect/resource data base to identify and utilize the otherwise harmful resources. The contributions of this research include: (1) Establishing a systematic process to identify, analyze and use harmful resources converting the harmful situations into useful situations in new application scenarios. (2) Establishing a set of systematic process and structured forms with examples and usage instructions to facilitate practical applications of the tools.